2006
DOI: 10.1097/01.aog.0000235709.55395.6a
|View full text |Cite
|
Sign up to set email alerts
|

Resident Physiciansʼ Competencies and Attitudes in Delivering a Postnatal Diagnosis of Down Syndrome

Abstract: II-3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 10 publications
(13 reference statements)
2
27
0
4
Order By: Relevance
“…Upon their child's diagnosis, parents should be given information about symptoms and health complications of DS so that they can recognise and understand these features and seek appropriate support and treatment where necessary for the optimal well-being of the child (Skotko et al 2009). Such information provision could be improved by ensuring HCPs in Pakistan are trained with up to date, accurate knowledge of DS and are able to communicate this in a sensitive manner, where parents can understand the implications for their child (Choi et al 2011;Ferguson et al 2006;Skotko et al 2009). There are challenges in providing information about DS because of the variability of the symptoms and severity of the condition.…”
Section: Discussionmentioning
confidence: 99%
“…Upon their child's diagnosis, parents should be given information about symptoms and health complications of DS so that they can recognise and understand these features and seek appropriate support and treatment where necessary for the optimal well-being of the child (Skotko et al 2009). Such information provision could be improved by ensuring HCPs in Pakistan are trained with up to date, accurate knowledge of DS and are able to communicate this in a sensitive manner, where parents can understand the implications for their child (Choi et al 2011;Ferguson et al 2006;Skotko et al 2009). There are challenges in providing information about DS because of the variability of the symptoms and severity of the condition.…”
Section: Discussionmentioning
confidence: 99%
“…These projects were funded by federal grants and efficacy was researched and published. 66,67 Down syndrome healthcare guidelines. "Healthcare Supervision for Children with Down Syndrome" (http:// pediatrics.aappublications.org/content/128/2/393).…”
Section: Provider Resourcesmentioning
confidence: 99%
“…The residents' knowledge and comfort levels were assessed by using pre and post-test with an education CD-ROM. 7 After 6 years, DSI has been modified by Lunney et al and has been accepted as a research with web-based tutorial. In that study, Lunney has found the mean discomfort levels of residents 23.05 with the highest discomfort level 35.…”
Section: Discussionmentioning
confidence: 99%
“…Optimistic feelings encourage healthy parent child relationship and optimal emotions, growth and development. 13 The post-tests in Lunney and Ferguson researches' have shown that the comfort levels of residents have increased with the educations by CD-ROM or web-based tutorial 7 . Our survey differed from the original in that we could not test the knowledge level of residents about DS due to a technical impossibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation